Papel da microbiota e efeito da administração oral de probiótico na toxoplamose experimental murina - Bruna Bernardo Nascimento (2015)
Toxoplasmosis is one of the most common worldwide zoonosis caused by Toxoplasma gondii, which provokes one of the most potent pro-inflammatory innate responses among all infectious diseases. Inflammation and infection intestinal are often accompanied by imbalance of the intestinal tract, which can generate an exacerbated inflammatory response. The intestinal microbiota plays an important role in maintaining homeostasis within the host and can protect the latter against infection by pathogenic agents. We intend to study the host parasites relationships using a germ-free (GF) animal model. Also, therapies that modulate the microbiota like probiotics are capable of improving the intestinal microbial balance, and when administered in sufficient quantities, are able to confer beneficial effects resulting in increased resistance against pathogens. The objective of this study was to evaluate the role of microbiota and the effect of the administration of probiotics in murine experimental toxoplasmosis. The survival rates of conventional (CV) and germ-free (GF) animals orally infected by T. gondii, did not present statistical difference. However, the development of disease in both animals assumed distinct forms. CV infected animals presented increased intestinal permeability, severe colitis and modification of pro-inflammatory intestinal cytokines but GF infected animals did not increase intestinal permeability and only slightly modificated the intestinal mucosa. The lesions were more severe in liver and brain of CV animals. Both groups had significant lung injuries what could explain the similar mortality index. In our studies we used two probiotics (Saccharomyces boulardii (SB) and Escherichia coli Nissle 1917 (EcN)) which were administered orally to CV animals, at a daily dose of 108 CFU/mL (for 10 days before infection and 8 days after infection). The animals were infected with 10 cysts of T. gondii. The animals treated with SB showed increased survival, inhibition of weight loss, decreased intestinal permeability, and clear and measurable protection from intestinal lesions caused by the parasite, in addition to protection from pulmonary lesions. However, EcN-treated animals showed no protection in survival and weight loss, and showed no protection against pulmonary lesions despite enabling the reduction of intestinal permeability, and protection against intestinal lesions. Treatment with SB produces a local and systemic immunomodulation, whereas treatment with EcN was only able to make local changes after infection with the strain (TgCTBr07) T. gondii.